Recent advances in production and upgrading of bio-oil from biomass: A critical overview - Baloch, H.; Nizamuddin, S.; Siddiqui, M.; Riaz, S.; Jatoi, A.; Dumbre, D.; Mujawar, Mubarak; Srinivasan, M.; Griffin, G. (Elsevuer BV, 2018)
© 2018 Elsevier Ltd. All rights reserved. Pyrolysis and liquefaction are widely accepted methods used for the synthesis of bio-oil using biomass. The quality and quantity of the bio-oil, produced either from pyrolysis or liquefaction, depend on various parameters including reaction temperature, reaction time, type of solvent and its ratio to biomass, lignocellulosic composition of feedstock and catalyst. Comparatively, hydrothermal liquefaction (HTL) is considered as more economic and environmental friendly process than pyrolysis. For instance, pyrolysis emits volatile matter and requires a dry feedstock while HTL can handle both dry and wet biomass, hence, saving costs, energy and time required for drying the biomass. The bio-oil cannot be used directly for transportation and ignition purposes. Therefore, it needs an upgrading process to improve its physico-chemical properties. There are various methods for upgrading of bio-oil such as hydro-treatment, catalytic cracking, supercritical fluid (SCFs), esterification and emulsification. This review describes the HTL process for biomass and its important parameters in detail, and various techniques employed for upgrading of bio-oil. The review also summarizes the effect of biomass feedstock source and composition on the process and products.